Engaging Patients and Other Stakeholders in “Designing for Dissemination” of Record Linkage Methods and Tools - Reno, Jenna E.; Ong, Toan C.; Voong, Chan; Morse, Brad; Ytell, Kate; Koren, Ramona; Kwan, Bethany M. (Applied Clinical Informatics, 2023)
Background Novel record linkage (RL) methods have the potential to enhance clinical informatics by integrating patient data from multiple sources—including electronic health records, insurance claims, and digital health devices—to inform patient-centered care. Engaging patients and other stakeholders in the use of RL methods in patient-centered outcomes research (PCOR) is a key step in ensuring RL methods are viewed as acceptable, appropriate, and useful. The University of Colorado Record Linkage (CURL) platform empowers the use of RL in PCOR.Objectives This study aimed to describe the process of engaging patients and other stakeholders in the design of an RL dissemination package to support the use of RL methods in PCOR.Methods Customer discovery, value proposition design, and user experience methods were used to iteratively develop an RL dissemination package that includes animated explainer videos for patients and an RL research planning workbook for researchers. Patients and other stakeholders (researchers, data managers, and regulatory officials) were engaged in the RL dissemination package design.Results Patient partners emphasized the importance of conveying how RL methods may benefit patients and the rules researchers must follow to protect the privacy and security of patient data. Other stakeholders described accuracy, flexibility, efficiency, and data security compared with other available RL solutions. Dissemination package communication products reflect the value propositions identified by key stakeholders. As prioritized by patients, the animated explainer videos emphasize the data privacy and security processes and procedures employed when performing research using RL. The RL workbook addresses researchers' and data managers' needs to iteratively design RL projects and provides accompanying resources to alleviate leadership and regulatory officials' concerns about data regulation compliance.Conclusion Dissemination products to promote adoption and use of CURL include materials to facilitate patient engagement in RL research and investigator step-by-step decision-making materials about the integration of RL methods in PCOR.
Keywords: record linkage; dissemination; patient engagement; stakeholder engagement; patient-centered outcomes research